Understanding signal integrity - Thierauf, Stephen C. (Artech House, 2011)
This unique book provides you with practical guidance on understanding and interpreting signal integrity (SI) performance to help you with your challenging circuit board design projects. You find high-level discussions of important SI concepts presented in a clear and easily accessible format, including question and answer sections and bulleted lists. This valuable resource features rules of thumb and simple equations to help you make estimates of critical signal integrity parameters without using circuit simulators of CAD (computer-aided design). The book is supported with over 120 illustrations, nearly 100 equations, and detailed reference lists at the end of each chapter.